Understanding and Responding to ‘Iatrogenesis’ - Timilsina, Digvijay S. (Nepal Journal of Neuroscience, 2005)
In the usual circumstances, medical treatment helps the patient recover from the illness. However, on occasions, medical intervention does harm rather than good. This review is an attempt to analyze the factors leading to medical harm to the patients. Nepal Journal of Neuroscience, Volume 2, Number 1, 2005, Page: 7-11